2001
DOI: 10.1291/hypres.24.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TCV-116 on Endothelin-1 and PDGF A-Chain Expression in Angiotensin II-Induced Hypertensive Rats.

Abstract: Angiotensin II (Ang II) has been shown to stimulate cardiac growth and collagen synthesis in cultured vascular smooth muscle cells and to increase fibroblast proliferation. Chronic infusion with Ang II increases blood pressure and activates growth mechanisms to produce hypertrophy of the heart. This study investigated the effects of an Ang II type 1 receptor antagonist, TCV-116, on preproendothelin-1 (preproET-1), ETA receptor and platelet-derived growth factor (PDGF) A-chain expression in the left ventricle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition, we have reported that up-regulated preproET-1, endothelin A receptor, and platelet-derived growth factor (PDGF) A-chain mRNA expression in Ang II-induced hypertensive rats were significantly decreased by a subdepressor dose of candesartan (1 mg/kg/day). Moreover, after 2 weeks of treatment, candesartan effectively improved left ventricular hypertrophy and cardiovascular structural changes, and decreased type I collagen mRNA expression, possibly due to a decrease in preproET-1, endothelin A receptor, and PDGF A-chain mRNA expression in the LV (Hara et al, 2001). Therefore, in the present study, these results suggested that cardiovascular remodeling in Ang II-induced hypertensive rats was significantly ameliorated by a subdepressor dose of candesartan, which may be in part mediated by an increase in eNOS expression and a decrease in ET-1 and PDGF A-chain expression in the LV.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, we have reported that up-regulated preproET-1, endothelin A receptor, and platelet-derived growth factor (PDGF) A-chain mRNA expression in Ang II-induced hypertensive rats were significantly decreased by a subdepressor dose of candesartan (1 mg/kg/day). Moreover, after 2 weeks of treatment, candesartan effectively improved left ventricular hypertrophy and cardiovascular structural changes, and decreased type I collagen mRNA expression, possibly due to a decrease in preproET-1, endothelin A receptor, and PDGF A-chain mRNA expression in the LV (Hara et al, 2001). Therefore, in the present study, these results suggested that cardiovascular remodeling in Ang II-induced hypertensive rats was significantly ameliorated by a subdepressor dose of candesartan, which may be in part mediated by an increase in eNOS expression and a decrease in ET-1 and PDGF A-chain expression in the LV.…”
Section: Discussionmentioning
confidence: 94%
“…Candesartan cilexetil as well as other angiotensin II antagonists have shown a considerable benefit controlling VSM growth and modulating extracellular protein synthesis in different tissues. [40][41][42][43] It is worth mentioning that many characteristics of the CSM are similar to those of VSM; therefore potential pathophysiologic projections, particularly for the use of selective angiotensin II blocking agents, have gained importance.…”
Section: Discussionmentioning
confidence: 99%
“…23 The beneficial effect of trandolapril and candesartan cilexetil on urinary ET-1 levels may be, in part, due to reduced intraglomerular pressure. Hara et al 24 reported that myocardial remodeling in angiotensin IIinduced hypertension in rats was significantly ameliorated by candesartan cilexetil and this may have been due to a decrease in ET-1 expression in the left ventricle. Angiotensin II was reported to enhance ET-1 synthesis in cultured endothelial cells.…”
Section: Discussionmentioning
confidence: 99%